1 Why is cold air associated with increased susceptibility to myocardial ischaemia?. (24th April 2016) - Williams, R; Asrress, K; de Waard, G; Lumley, M; Arri, S; Patterson, T; Ellis, H; Briceno, N; Khawaja, Z; Chiribiri, A; Clapp, B; Plein, S; et al.
Abstract : Introduction: Cold air inhalation (CAI) during exercise increases cardiac mortality. The pathophysiology remains unclear, but may reflect adverse changes in microvascular resistance (MVR). We compared the accuracy of two novel intra-coronary measures of MVR to predict microvascular dysfunction (MVD). We then used the best MVR measure to quantify changes during CAI, exercise alone and exercise with CAI. Methods: 56 patients (74 arteries: post PCI or FFR >0.8) had hyperaemic microvascular resistance (hMR) and index of microcirculatory resistance (IMR) compared against: Coronary flow reserve (CFR) CMR perfusion CMR microvascular obstruction (MVO). In a further 55 patients (45 with coronary artery disease (CAD), baseline and peak MVR was measured after 5 min of either: CAI (-15 o C) Cycling CAI during cycling. Results: hMR had better diagnostic accuracy than IMR to predict CFR (AUC 0.82 vs. 0.58), CMR perfusion (AUC 0.85 vs. 0.72) and MVO (AUC 0.83 vs. 0.72) (Figure 1, Study 1). CAI at rest decreased MVR in patients with normal coronaries but increased MVR in CAD patients (p < 0.01) (Figure 1, Study 2). In CAD patients, cycling caused an adaptive decrease in MVR (p < 0.0001), but CAI during cycling abolished this decrease (Figure 1, Study 2). Conclusions: hMR is a better predictor of MVD than IMR. CAI causes adverse changes in MVR in CAD patients both at rest and during exercise, rendering the heart more susceptible to ischaemia.